The use of induction motor line current harmonics in drive system applications: A survey - Guldemir, Hanifi; Gokbulut, Muammer (My University, 2004)
The line current spectrum of an induction motor normally contains a variety of harmonics of different magnitudes and frequencies from a variety of different sources. Signal processing techniques are used to extract the useful information contained in the line current harmonics. In this paper several different applications of induction motor line current spectrum are reviewed. First, the origin and the producing mechanism of the line current harmonics and the factors which affect these harmonics are explained. Then the applications of these harmonics from sensorless speed control to condition monitoring are explained.
Keywords: Airgap field; Condition monitoring; Line current spectrum; Speed prediction